The evolving concept of access to justice in Singapore’s mediation movement - Dorcas QUEK ANDERSON, (Institutional Knowledge at Singapore Management University, 2020)
This article examines the key societal developments underpinning the growth of mediation in Singapore with the view to analysing the evolving conceptualisation of justice within mediation. The introduction of mediation corresponded with a shift from adversarial justice to an indigenous form of conciliatory justice, in which a respected mediator played an advisor role to the disputants and was trusted to ensure the fairness of the process. However, this trajectory was tempered by the need to ensure that Singapore mediation practice conformed with international practices concerning the protection of parties’ autonomy. The ambivalence concerning the mediator’s role has resulted in uncertainty about whether the mediator bears primary responsibility for ensuring procedural and substantive fairness. The article discusses the implications of this ambiguity and proposes ways to resolve it. The current phase of professionalisation in Singapore’s mediation movement offers the opportune moment to resolve these existing tensions and to crystallise the mediator’s role in facilitating access to justice.